Assessing Policies, Practices and Impact of Actions and Policies in Handling Covid-19 Pandemic: Comparative Studies of Bangladesh and Indonesia - Sherajum Munira; Sidik Jatmika (Universitas Muhammadiyah Yogyakarta, 2022)
This article aims to describe how Bangladesh and Indonesia face problems of good governance, especially aspect accountability, when conduct health diplomacy and communicatian in handle Covid-19 issues. This is qualitative research and constructivism approach, which using the content analysis method to find out such of Banglkdesh and Indonesian government statements, policy and action in handling Covid-19 pandemic crisis. The article found that Bangladesh and Indonesia governments face such of problems of health diplomacy and political communication with international communities; inter-governmental institution and citizens. These problems especially come from ‘low-level skill of health diplomacy and communication” in which central-government as prominent ccommunicator, express such as health message or policy in ‘uncredible’ ways of both governments. This situation has contributed to make policy to stop Covid-19 to be more complicated. By using content analysis, the article found that both of Bangldesh Indonesian developed in a “un- smart”, “un-systematic”, “un-objective”, and “un- visionary” way in handle diplomacy and communication in global health crisis. It shows how important of good governance of health diplomacy and communication, including prepareness in health disasster mitigation in a country to handle such of effects of global health crisis.